QREEN Application to Address Water Supply Challenges in Blora Regency - Sahrin, Alfin; Akhiriyanto, Novan; Utami, Erna; Handoko, Susilo (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Seasonal dry periods in Blora Regency routinely lead to drought conditions, which make it difficult for communities to secure clean water for daily use and for agricultural irrigation. This community service initiative aimed to deliver a rapid energy-based solution by implementing the Quick Response Energy (QREEN) system to support water distribution and environmental lighting in Ledok, Temengeng, and Joho Villages. The program followed a community based participatory approach with five stages, namely problem identification grounded in field data, technology solution design, site selection, implementation coordination, and program evaluation. Using a mixed methods design, data were collected through direct observation, semi structured interviews, and quantitative surveys administered to selected users. The results indicated high user satisfaction, including improved ease of access to clean water (79 to 85%) and time savings (75 to 83%), as well as increased farming yields (72 to 80%) among users who manage agricultural land. Overall, the findings suggest that QREEN implementation can strengthen local water security, although the magnitude of impact varies across contexts. Sustained, cross sector collaboration is recommended to support long term operation and enable program expansion.